2019
DOI: 10.1016/j.nicl.2019.102046
|View full text |Cite
|
Sign up to set email alerts
|

EEG time signature in Alzheimer´s disease: Functional brain networks falling apart

Abstract: HighlightsEEG microstate topographies differ between controls and memory clinic patients.Microstate parameters differ in a gradient-like manner in SCD, MCI and AD patients.Changes in topography of microstate class C correlate with CSF Aβ42 levels.Changes in topography of microstate class B correlate with CSF p-tau levels.EEG microstates detect early disruption of neurocognitive networks in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 60 publications
6
47
0
2
Order By: Relevance
“…The topography of microstate class D was altered in AD. Previous studies give conflicting reports on alterations to microstate topographies in AD; in agreement with our results, Smailovic et al 29 found alterations to the topography of class D in AD but also found alterations to class A, while Schumacher et al 28 found alterations to all classes in AD and Nishida et al 26 found alterations to none. Differences in the number of channels is unlikely to explain these inconsistencies in results, as microstates are reliable with 8 or more channels 43 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The topography of microstate class D was altered in AD. Previous studies give conflicting reports on alterations to microstate topographies in AD; in agreement with our results, Smailovic et al 29 found alterations to the topography of class D in AD but also found alterations to class A, while Schumacher et al 28 found alterations to all classes in AD and Nishida et al 26 found alterations to none. Differences in the number of channels is unlikely to explain these inconsistencies in results, as microstates are reliable with 8 or more channels 43 .…”
Section: Discussionsupporting
confidence: 86%
“…Alterations to patterns of transitions between classes have also been reported in neurological disease 26 , 27 , suggesting that studying transitioning behaviour of microstates may give further mechanistic insights into cognitive impairment in AD as well as increasing sensitivity of electrophysiological biomarkers. Indeed, recent studies have identified alterations to spatial patterns and temporal dynamics of EEG microstates in AD and MCI 17 , 26 , 28 , 29 . However, the ‘syntax analysis’ 26 , 27 used to analyse transitioning behaviour in these studies assumes the next microstate depends only on the present microstate (Markovian), and probabilities of transitions do not change over time (stationary).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, quantitative EEG analysis provides the most direct and dynamic clinical representation of neuronal and synaptic function in AD patients; however, while it is sensitive to changes in neuronal circuit responses resulting from synaptic dysfunction, it cannot discriminate between the exact mechanisms of action underlying synaptic dys/function. Alterations in quantitative measures derived from EEG data in patients with AD have been widely described and have been shown to be sensitive to disease progression [134,138,139] and to correlate with CSF biomarkers of AD [140]. Furthermore, EEG is non-invasive, robust, efficacious, and widely available in hospitals.…”
Section: Biomarkers Of Synapse Damage or Lossmentioning
confidence: 99%
“…To measure phase synchronization, the characteristics of synchronous signals can be quantitatively estimated at different detection points by calculating the PLI. Firstly, the EEG signals were divided into 5 frequency bands: delta (2-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma . Each band-divided signal at time t and point a is represented by the phase fa (t) and the amplitude Aa (t) via the Hilbert transform.…”
Section: Phase Lag Indexmentioning
confidence: 99%
“…Among these methods, those based on EEG are highly effective in clinical application, because they are cost-effective, widely available, and non-invasive (14,15). The pathological progression of AD leads to cortical disconnection; consequently, in EEG signals, it alters functional connectivity measured by the degree of synchronization between different brain regions and complex behavior produced by the interactions among wide spread brain regions (9,11,12,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%